The Effect of Training on Employee Performance at PT. Asuransi Bintang Tbk, Jambi Branch - Almaududi, Said (Dinasti International Journal of Management Science, 2025)
This study aims to examine the effect of training on employee performance at PT. Asuransi Bintang Tbk Cabang Jambi. This research is quantitative descriptive research used to test hypotheses. The research sample consists of employes from PT. Asuransi Bintang Tbk Jambi Branch, with a population of 55 persons, utilizing the population census method as respondents to answer the questionnaire. The data collection technique employed is questionnaires. The data analysis technique utilized is SPSS with simple regression analysis and t-test. Training (X) and Performance (Y) at PT. Asuransi Bintang Tbk Jambi Branch are positively correlated, according to the SPSS calculation Y=0.809+0.696X+e. This figure of 0.299 from the SPSS results (coefficients) shows that the Training variable (X) may explain the Performance variable (Y) by 29.90%, with other factors not included in the study model accounting for the remaining 70.10%. Partially, training has an influence on the performance of PT. Asuransi Bintang Tbk Jambi Branch. The study's conclusion is that, overall, training has a beneficial impact on employee performance. Based on hypothesis testing, a substantial positive link was discovered between training and employee performance.